Why I am so very unFrench, and other essays - Jacques Bouveresse (Collège de France, 2013)
For those like myself, who found the politico-philosophical terrorism beginning its reign at the beginning of the 1960s intolerable, analytic philosophy in contrast could not but offer the comforting image of what a democratic philosophical community should be: civilized and tolerant, where all citizens equally must offer arguments and be willing to listen to and discuss possible objections. This sort of community was the last thing we could hope to ask for in the philosophical milieu of that...